THE EFFECT OF A COMBINATION OF OXYTOCIN MASSAGE, LACTATION MASSAGE AND ACUPRESSURE ON POSTPARTUM MOTHER'S MILK PRODUCTION 0-3 DAYS - Meilawati, Mutia Dewi; Gapmelezy, Ezzy (HEARTY, 2024)
According to the Jakarta Provincial Health Office report of 2023, the exclusive breastfeeding coverage in DKI Jakarta province was 50.11% in 2022. In South Jakarta, the exclusive breastfeeding coverage rate was 50.32% in the same year. Although these coverage rates are already significant, there are still many mothers who do not exclusively breastfed their children. One of the reasons for the failure of exclusive breastfeeding is the delay in breast milk production during the first three days after delivery, leading mothers and families to resort to formula milk.(Aprilianti, 2019) The objective of this study is to determine the effects of a combination of oxytocin massage, lactation massage, and acupressure on breast milk production in postpartum mothers within 0-3 days of delivery at TPMB Yevi Yesevi, AMd., located in the South Jakarta District in December 2023. The research aims to provide knowledge and insights to the public regarding massage techniques that can increase breast milk production. Quantitative research methods were employed in this study, using a pre-experimental design and the one-group pretest and posttest technique. The population for this research consisted of postpartum mothers within 0-3 days of delivery at TPMB Yevi Yesevi, AMd.Keb. A non-probability sampling procedure with purposive sampling technique was utilized, resulting in a sample size of 30 respondents. Data analysis involved univariate and bivariate analysis using the Wilcoxon Test. The results of the pretest showed a mean of 0.61, a median of 0.35, , and a standard deviation of 0.6502. On the posttest, the results showed a mean, median, and standard deviation of 2.6, 2.60, and 1.3564, respectively. The Wilcoxon test analysis revealed a Z value of -4.579 and an asymptotic value of significance (2-tailed) of 0.000, which is smaller than the alpha level of 5% (0.05). Hence, Ha is accepted, and H0 is rejected. Therefore, it can be concluded that there is a significant influence of the combined action of oxytocin massage, lactation massage, and acupressure on breast milk production in postpartum mothers within 0-3 days.